Higher C-Peptide Level During Glucose Clamp Is Associated With Muscle Insulin Resistance in Nonobese Japanese Men - Kaga, Hideyoshi; Tamura, Yoshifumi; Takeno, Kageumi; Kakehi, Saori; Someya, Yuki; Funayama, Takashi; Furukawa, Yasuhiko; Suzuki, Ruriko; Sugimoto, Daisuke; Kadowaki, Satoshi; Nishitani-Yokoyama, Miho; Shimada, Kazunori; et al. (Journal of the Endocrine Society, 2019)
ContextCirculating C-peptide is generally suppressed by exogenous insulin infusion. However, steady-state serum C-peptide (SSSC) levels during hyperinsulinemic-euglycemic clamp in obese subjects are higher than in healthy subjects, which may contribute to hyperinsulinemia to compensate for insulin resistance. Even in healthy subjects, interindividual variations in SSSC levels are present; however, the characteristics of subjects with high SSSC levels in those populations have not been fully elucidated.ObjectiveTo investigate the clinical parameters associated with interindividual variations in SSSC levels in apparently healthy, nonobese Japanese men.Design and ParticipantsWe studied 49 nonobese (BMI < 25 kg/m2), healthy Japanese men. We evaluated SSSC and insulin sensitivity using hyperinsulinemic-euglycemic clamp with tracer. Intrahepatic lipid (IHL) was measured using proton magnetic resonance spectroscopy.ResultsWe divided subjects into high and low SSSC groups based on the median SSSC value and compared their clinical parameters. Compared with the low SSSC group, the high SSSC group had IHL accumulation, impaired muscle insulin sensitivity, reduced insulin clearance, and hyperinsulinemia during a 75-g oral glucose tolerance test (OGTT). All of these factors were significantly correlated with SSSC.ConclusionsIn healthy, nonobese men, higher SSSC was associated with impaired muscle insulin sensitivity, IHL accumulation, and hyperinsulinemia during OGTT. These findings suggest that higher endogenous insulin secretion during hyperinsulinemia, along with reduced insulin clearance, may be an early change to maintain metabolic status in the face of moderate muscle insulin resistance, even in healthy, nonobese men.